“Propagación in vitro de cedro (cedrela odorata L.) Vía organogenésis” - Huamán Cachique, Guadalupe Ximena (2014)
Since many decades, forest species coming retaking additive importance. Selective activities in overexploitation practicad during the 80s in the Amazonian regions have to generate great disturbance on population distribution, placing at risk habitats or places of origin. Cedro (Cedrela odorata L.), one of the target species, carne to be considered since 1981 as a priority species for conservation (Lahey, 1995), numerous efforts were made to conservation and/or multiplication, basic research were development on aspects genetics and physiological. Basad about thls efforts and focusing in growth regulators (phytohormones), were tested different doses of ANA (0.00, 0.53 and 1.43 μM) and BAP (2.21, 4.43 and 8.87 μM) on nodal segments from in vitro plants (started by botanical seeds). Events of rnorphological response observed in plant rise, number of leaves, number of nades, number and lengthof roots, reported that: no or low concentrations of ANA (0.00 to 0.53 μM) increase the longitudinal growth of roots and increased number of leaves; also, BAP concentrations (2.21 μM) stimulated predominantly lateral shoot, growth and formation root; the increase in the number of leaves in duplicate concentration (4.43 μM). Moreover, ANA concentrations (0.53 μM) and BAP (2.21 μM) in mutual function, act synergistically on the growth and development of root and stem; being that, the absence of ANA and BAP duplication (4.33 μM) acts positively on the number of nodes and leaves. Exist an essential role of 6-benzylaminopurine (BAP) on the growth and development of segment nodal of cedro.